Navigating miscarriage in Jordan: understanding emotional responses and coping strategies - Esra' Taybeh; Shereen Hamadneh; Zina Al-Alami; Rana Abu-Huwaij (BMC, 2023)
Abstract Background Miscarriages account for 20% of clinically confirmed pregnancies and up to 50% of all pregnancies and is considered one of the most heartbreaking events experienced by women. The current study aimed to explore participants' perceptions and practices and how they link with the negative emotions of miscarriage. Methods In this cross-sectional study a web-based questionnaire was used to gather data from 355 women living in Jordan who had experienced a previous miscarriage. The questionnaire consisted of four sections, including socio-demographic information, experience with miscarriage, emotions after the experience, and self-care practices. Participants were recruited through social media platforms from April to August 2022. Data were analyzed using SPSS, and descriptive statistics, chi-square test, and binomial regression were performed to examine the results. Results The results show that the majority of participants were in the age group of 22-34 years and a larger percentage of participants hold a Bachelor's degree and were employed. All participants had experienced a previous miscarriage with 53.8% having one, 27.0% having two, and 19.2% having three or more miscarriages. In addition, most miscarriages did not have an explanation for their cause (77.5%), but vaginal bleeding was the most reported symptom (55.2%) and surgical management was predominant (48.7%). Most participants reported adequate emotional support from partners and family (63.7% and 62.3%, respectively). Almost half (48.7%) of the respondents felt like they had lost a child and those who did not receive any social support had a higher association with the same feeling (p = 0.005). Of the participating women, 40.3% decided to postpone another pregnancy while 20.0% planned for a subsequent pregnancy. The feeling of shame regarding the miscarriage was the main driver for women to get pregnant again (Odd ration [OR] 2.98; 95% confidence interval (CI) 1.31-6.82; p = 0.01). Conclusions The findings highlight the emotional impact of miscarriage on women and the need for proper support and self-care practices.